1998
DOI: 10.1200/jco.1998.16.6.2261
|View full text |Cite
|
Sign up to set email alerts
|

Resection of metastatic renal cell carcinoma.

Abstract: Selected patients with recurrent RCC who can undergo a curative resection of their disease have a good opportunity for long-term survival, particularly those with a single site of recurrence and/or a long DFI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
292
1
14

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 512 publications
(329 citation statements)
references
References 43 publications
13
292
1
14
Order By: Relevance
“…Several non-comparative studies suggest that the disease dynamic might be more important than any intervention. Low tumour grade 39 and long metachronous intervals with repeat resection 40 are associated with long survival. No reliable data exist on the proportion of patients with metastatic renal cell carcinoma who would be eligible for local treatment of their metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Several non-comparative studies suggest that the disease dynamic might be more important than any intervention. Low tumour grade 39 and long metachronous intervals with repeat resection 40 are associated with long survival. No reliable data exist on the proportion of patients with metastatic renal cell carcinoma who would be eligible for local treatment of their metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with widely metastatic disease or who choose not to have surgical intervention can expect a 5-year survival of only 5% to 30%. 35,36 It is likely that surgical intervention for solitary pancreatic metastasis from RCC provides a survival benefit, although such benefit may be due to both the extent of disease and the surgical resection. 5,20,33,37,38 Lung Cancer Lung cancer is the most common cause of cancerrelated death in the United States.13 Lung cancer is typically classified as either small cell lung cancer (SCLC) or non-small cell lung cancer (NSCLC: squamous cell carcinoma, adenocarcinoma, and large cell carcinoma), based on pathologic parameters.…”
mentioning
confidence: 99%
“…Several retrospective studies have suggested that patients undergoing complete resection of isolated metastatic focus may experience long disease-free intervals, with median overall survival rates of 35 % to 50 % in some reports. [1] In metastatic renal cell cancer, surgical management includes the cytoreductive nephrectomy with metastasectomy. But before contemplating surgery with a curative intent the staging investigations other than multiphasic abdomino-pelvic Fig.…”
Section: Discussionmentioning
confidence: 99%